A masterplan for urban resurgence: The case of Mönchengladbach, Germany (2008–2019) - Anna Herzog; Rüdiger Hamm (Regional Science Policy & Practice, 2021)
This paper investigates how an urban masterplan can be used to catalyse civic and entrepreneurial engagement to trigger a broad resurgence process within a medium-sized city. Therefore, it dwells on the masterplan project MG 3.0 in Mönchengladbach, which is often described as the initial impulse of a dynamic resurgence process—a confident statement the authors want to question. The exploratory case study applies the “urban health” concept by Glaeser and Gottlieb and highlights the significance of place-based leadership as well as entrepreneurial engagement in terms of Corporate Urban Responsibility in developing an overarching vision of the urban future.
Keywords: 320; corporate urban responsibility; masterplan; Mönchengladbach; place-based leadership; resurgence